Eosinophilic Gastritis as an Intriguing Case of Gastric Outlet Obstruction in a Female Toddler: A Case Report - Amanjot Kaur; Kanojiya Atul Ghanshyam; Sarthak Chakrabarti; Ashok Singh; Yash Shrivastava; Nowneet Kumar Bhat (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2026)
Background Eosinophilic gastritis (EoG) is an uncommon form of eosinophilic gastrointestinal disease (EGID) characterized by dense eosinophilic infiltration of the gastric wall, most often involving the antrum and fundus. Although EoG can mimic other causes of gastric outlet obstruction (GOO), including infantile hypertrophic pyloric stenosis (IHPS), such presentations are rare. Diagnosis requires histological confirmation, and management typically involves dietary modification with elimination diets, corticosteroids, and proton pump inhibitors. Case: We report the case of a 3-year-old girl presenting with recurrent non-bilious, non-bloody projectile vomiting and abdominal pain over 15 days, with a 3 kg weight loss. Imaging revealed pyloric canal hypertrophy not meeting IHPS criteria, and upper gastrointestinal endoscopy showed an erythematous, edematous antrum with pinpoint pylorus. Pyloric biopsy demonstrated dense eosinophilic infiltration (>30 eosinophils/HPF in 5 fields), confirming EoG. The child was treated with oral prednisolone (2 mg/kg/day) and lansoprazole (1 mg/kg/dose twice a day), resulting in marked clinical improvement and weight gain within two weeks Discussion: EoG represents a spectrum of EGIDs, with clinical manifestations depending on the gastric layer involved. It may occur with or without peripheral eosinophilia and is frequently associated with atopic conditions. Diagnosis rests on gastrointestinal symptoms, tissue eosinophilia, and exclusion of secondary causes. Corticosteroids remain the cornerstone of treatment, though dietary elimination and PPIs also contribute to remission. Conclusion: EoG should be considered in children presenting with unexplained GOO. Early endoscopic biopsy and corticosteroid-based therapy can lead to rapid symptom resolution and prevent long-term morbidity.